Optimization method for enhancing aluminum-based resin material through temperature-mediated carbon fiber surface modification

Through temperature-mediated carbon fiber surface modification and nano-aluminum powder dispersion technology, the problems of insufficient interface binding force between carbon fiber and resin matrix and uneven distribution of nano-aluminum powder are solved, and the mechanical properties and thermal conductivity of the composite material are significantly improved.

CN119463230AInactive Publication Date: 2025-02-18马海洪
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411524928.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the interface bonding force between carbon fiber and resin matrix is ​​weak, which can easily lead to layering or fracture of composite materials under mechanical action. At the same time, the nano-aluminum powder is unevenly distributed in the resin, affecting the thermal conductivity of composite materials and Mechanical properties.

Method used

Through a temperature-mediated carbon fiber surface modification method, agated functionalized graphene nanosheet coating and plasma enhanced chemical vapor deposition (PECVD) technology are used to increase the functionalized layer and nitrogen-containing carbon nanofilm on the carbon fiber surface, and through Carboxylation treatment and ultrasonic dispersion technology improve the dispersion of nano-aluminum powder.

Benefits of technology

It significantly improves the interface bonding force between carbon fiber and resin, enhances the mechanical properties and thermal conductivity of composite materials, reduces stratification and fracture phenomena, and is suitable for the preparation of composite materials with high strength and high reliability requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463230A_ABST
    Figure CN119463230A_ABST
Patent Text Reader

Abstract

The invention relates to the field of aluminum-based resin materials, and discloses an optimization method for reinforcing an aluminum-based resin material through temperature-mediated carbon fiber surface modification, and the material formula comprises the following components: 35-45% by mass of carbon fiber, 10-20% by mass of carbon fiber, and 10-20% by mass of carbon fiber. Wherein the surface of the carbon fiber is modified through the following steps: coating the surface of the carbon fiber with an aminated functionalized graphene nanosheet with the mass ratio of 2%-5%; then depositing a layer of nitrogen-containing carbon nano-film on the surface of the carbon fiber through a plasma enhanced chemical vapor deposition (PECVD) method so as to increase the chemical activity of the interface; the heat treatment is carried out at the temperature of 200-300 DEG C to stabilize the surface structure and enhance the interface strength, the aluminum-based resin comprises the following components: 55% of bisphenol A type modified epoxy resin, and 5-10% by mass of aluminum phosphide nanoparticles are doped into the epoxy resin. By adopting amination functionalized graphene nanosheet coating and plasma enhanced chemical vapor deposition technologies, a more uniform surface structure with enhanced activity is obtained on the surface of the carbon fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aluminum-based resin materials, in particular to an optimization method for strengthening aluminum-based resin materials by temperature-mediated carbon fiber surface modification. Background Art

[0002] Aluminum-based resin materials are a type of composite materials with aluminum powder as filler and polymer materials such as epoxy resin or polyimide as the matrix. This type of material has excellent mechanical properties, high temperature resistance and excellent thermal and electrical conductivity, and is widely used in aerospace, automobile manufacturing, electronic packaging and other fields. In these applications, the high thermal conductivity of aluminum-based resin materials enables it to effectively dissipate heat. At the same time, its lower density and high strength give it significant advantages in lightweight and high-strength structures. Temperature-mediated carbon fiber surface modification technology is a method of improving the interfacial bonding performance between carbon fiber and resin matrix by controlling temperature and process steps. Carbon fiber, as a high-performance reinforcing material, has extremely high specific strength and specific modulus, and is resistant to high temperature and corrosion. It is widely used in the reinforcement field of composite materials. However, the interfacial bonding force between carbon fiber and resin matrix is ​​weak, which easily leads to delamination or fracture of composite materials under mechanical effects such as stretching and bending.

[0003] In the prior art, chemical oxidation (such as nitric acid or sulfuric acid treatment) and plasma treatment are usually used to modify the surface of carbon fiber to improve the interfacial bonding strength between the carbon fiber and the resin matrix. Although chemical oxidation treatment can introduce oxygen-containing functional groups (such as hydroxyl, carboxyl, etc.) to increase the polarity of the carbon fiber surface, this modification has limited effect on improving the interfacial bonding strength and is difficult to meet the demand for high-strength interfacial bonding. Chemical oxidation treatment can easily lead to local damage and increased roughness on the surface of the carbon fiber, thereby weakening the bulk properties of the carbon fiber, such as tensile strength and toughness.

[0004] In order to improve the thermal conductivity and electrical conductivity of composite materials, thermal and electrical conductive fillers such as nano-aluminum powder are often added to the resin matrix. However, in the prior art, the nano-aluminum powder is often dispersed using a traditional mechanical stirring process. Mechanical stirring is limited by the stirring speed and stirring method, and cannot completely break the agglomeration effect between nanoparticles, resulting in uneven distribution of aluminum powder in the resin, which in turn affects the thermal conductivity and mechanical properties of the composite material.

[0005] In order to overcome the deficiencies in the prior art, the present invention provides an optimization method for temperature-mediated carbon fiber surface modification to enhance aluminum-based resin materials. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides an optimization method for temperature-mediated carbon fiber surface modification to enhance aluminum-based resin materials, which solves the problem that chemical oxidation treatment easily causes local damage and increased roughness on the carbon fiber surface, thereby weakening the bulk properties of the carbon fiber, such as tensile strength and toughness.

[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials, wherein the material formula includes the following components:

[0008] Carbon fibers, in a mass ratio of 35% to 45%, wherein the surface of the carbon fibers is modified by the following steps:

[0009] Coating 2% to 5% by mass of amino-functionalized graphene nanosheets on the surface of carbon fibers;

[0010] Then, a nitrogen-containing carbon nanofilm was deposited on the carbon fiber surface by plasma enhanced chemical vapor deposition (PECVD) to increase the interfacial chemical activity;

[0011] Heat treatment at 200°C to 300°C to stabilize the surface structure and enhance interface strength;

[0012] Aluminum-based resin, comprising the following components:

[0013] 55% of bisphenol A modified epoxy resin, wherein 5% to 10% by mass of aluminum phosphide nanoparticles are added to the epoxy resin;

[0014] 20%-30% volume fraction of nano-aluminum powder, with a particle size of 10 to 50 nanometers;

[0015] 10% - 20% polyimide-based curing agent;

[0016] 1% - 3% silane coupling agent;

[0017] 5%-10% of a toughening agent, wherein the toughening agent comprises a mixture of carboxyl-terminated nitrile rubber (CTBN) and a fluorine-containing polymer.

[0018] Preferably, the amino-functionalized graphene nanosheets are coated on the surface of the carbon fiber by the following steps:

[0019] Placing the carbon fiber in an immersion tank filled with an amino-functionalized graphene nanosheet solution, wherein the immersion tank is made of corrosion-resistant stainless steel and equipped with a constant temperature control system to control the temperature at 25° C. to 30° C.;

[0020] The solution is evenly distributed and impregnated into the carbon fiber by a magnetic stirring device at room temperature, and the impregnation time is 30 to 60 minutes;

[0021] The impregnated carbon fiber is taken out and dried in a forced air drying oven at 100° C. to 150° C. for 1 to 2 hours.

[0022] Specifically, the carbon fiber is cut to a desired size and surface cleaned, and is cleaned in deionized water, ethanol and acetone solutions in turn using an ultrasonic cleaning device for 10 to 20 minutes each time to remove impurities and grease attached to the surface of the carbon fiber; subsequently, the cleaned carbon fiber is dried in a vacuum drying oven at 80°C to 100°C for 2 hours, and the dried carbon fiber is immediately placed in an impregnation tank containing an amino functionalized graphene nanosheet solution, wherein the impregnation tank is made of corrosion-resistant stainless steel material and is equipped with a constant temperature control system to control the temperature of the impregnation solution between 25°C and 30°C; at the same time, the solution in the impregnation tank includes an appropriate amount of deionized water and a dispersant to ensure a stable dispersion state of the graphene nanosheets in the solution The volume concentration of the dispersant is 1% to 3%. The solution is evenly stirred at a speed of 500 to 1000 revolutions per minute by a high-efficiency magnetic stirring device to make the amino-functionalized graphene nanosheets evenly distributed and fully contact with the carbon fiber surface. The immersion time is 30 to 60 minutes. During this process, the solution in the immersion tank needs to be continuously filtered by a circulating filtration system to prevent nanosheets from agglomerating or impurities from mixing in. After the impregnation is completed, the carbon fiber is taken out of the solution and preliminarily dried. Then, the carbon fiber is placed in a blast drying oven preheated to 100°C to 150°C for heat drying. The drying time is 1 to 2 hours to ensure that the amino-functionalized graphene nanosheets are firmly attached to the carbon fiber surface and form a uniform coating.

[0023] Preferably, the PECVD process comprises the following steps:

[0024] The carbon fiber coated with amino functionalized graphene nanosheets is placed in a PECVD reaction chamber, wherein the chamber is made of high-purity quartz material and has high vacuum sealing performance;

[0025] Using methane (CH4) and ammonia (NH3) as reaction gases, the flow ratio of methane to ammonia is 1:1 to 1:3;

[0026] Plasma is excited by a radio frequency power supply device, and nitrogen-containing carbon nanofilm is deposited on the surface of carbon fiber under low pressure (10^-2 to 10^-3 Torr) for 15 to 30 minutes.

[0027] Specifically, the carbon fibers coated with amino-functionalized graphene nanosheets are evenly arranged and placed in a PECVD reaction chamber, which is made of high-purity quartz material and has high vacuum sealing to ensure that external air or impurities are not intruded during the reaction; the initial pressure inside the chamber is reduced to 10^-5 to 10^-6 Torr by a high-precision vacuum pump system to remove residual gas; then, methane (CH4) and ammonia (NH3) are accurately introduced as reaction gases through a gas mass flow controller, and the flow ratio of methane to ammonia is controlled between 1:1 and 1:3, while the stable supply of reaction gas is ensured by continuously monitoring the gas concentration; then, a radio frequency power supply device is used to generate a charge and discharge gas; Plasma is excited with a radio frequency power of 13.56MHz to generate active hydrogen ions and nitrogen ions in the reaction chamber. These active particles react with amino-functionalized graphene nanosheets on the surface of carbon fiber under a low pressure environment of 10^-2 to 10^-3Torr. Through this plasma-induced deposition process, a layer of nitrogen-containing carbon nanofilm is deposited on the surface of carbon fiber layer by layer. The deposition time is 15 to 30 minutes, and the thickness and density of the film are controlled by adjusting the radio frequency power in the range of 50W to 200W. After the deposition is completed, the system automatically terminates the plasma and gradually returns to normal pressure to ensure that the carbon fiber is removed from the reaction chamber without contamination and is ready for subsequent processes.

[0028] Preferably, the heat treatment step comprises:

[0029] Use a high-temperature vacuum furnace, the furnace body is lined with high-temperature resistant graphite material and is equipped with an automatic temperature control system;

[0030] The PECVD-treated carbon fiber was placed in a vacuum furnace and heated at a vacuum degree of 10^-5 to 10^-6 Torr at a heating rate of 5°C / min.

[0031] When the temperature reaches 250°C, maintain this temperature for 1 to 2 hours and then slowly cool down to room temperature.

[0032] Preferably, the method comprises the following steps:

[0033] The modified carbon fiber is subjected to vacuum drying at a temperature of 80°C to 120°C for 1 hour;

[0034] An aluminum-based resin mixture is prepared, nano-aluminum powder is dispersed in a modified epoxy resin by ultrasonic treatment, and then aluminum phosphide nanoparticles, a polyimide-based curing agent, a silane coupling agent and a toughening agent are added and high shear mixing is performed;

[0035] Pre-curing the mixture at 100°C to improve the homogeneity of the mixture and fiber impregnation;

[0036] The pretreated carbon fiber is laminated with an aluminum-based resin mixture and initially cured at 80°C to 100°C in a vacuum environment.

[0037] Preferably, the preliminary curing and the second stage curing process include the following steps:

[0038] Use a programmable heat press equipped with a temperature and pressure control system that can precisely control the curing temperature and applied pressure;

[0039] In the initial curing stage, the composite material is placed in a hot press and cured at a temperature ranging from 80°C to 100°C for 1 to 2 hours;

[0040] After initial curing, the temperature of the composite material is raised to 120°C to 150°C and heated for 3 to 4 hours, while low-frequency vibrations of 40 to 60 Hz are applied through a built-in vibration generator to promote uniform distribution of aluminum powder and other nanoparticles in the resin matrix.

[0041] Specifically, a programmable hot press is used for curing treatment. The hot press is made of high-strength steel and is equipped with a precise temperature and pressure control system. It can accurately control the curing temperature and applied pressure according to the set program to ensure that the composite material is evenly heated and pressurized during the curing process. In the initial curing stage, the prefabricated composite material stacked structure is placed on the workbench of the hot press to ensure that each layer of material is closely aligned and avoids the presence of bubbles or gaps. Then, the vacuum system is started to reduce the ambient pressure to 10^-3 to 10^-4 Torr to prevent the formation of pores inside the material during the curing process. Then, the temperature of the hot press is set between 80°C and 100°C, the heating rate is controlled at 2°C / minute, and an initial pressure of 1 to 3MPa is applied. This temperature and pressure condition is maintained for 1 The composite material is subjected to preliminary curing for 2 to 2 hours in order to pre-crosslink the resin and improve the structural stability of the composite material; after the preliminary curing is completed, the temperature of the hot press is gradually increased to 120°C to 150°C, and the pressure is increased to 3 to 5MPa, and heating is continued for 3 to 4 hours under this condition to ensure that the resin is completely cross-linked and forms a final cured structure; during this process, a built-in vibration generator is used to vibrate the pressing plate of the hot press at a low frequency of 40 to 60Hz, and the vibration amplitude is maintained at 1 to 2mm to promote the uniform distribution of aluminum powder and other nanoparticles inside the composite material and prevent the occurrence of particle aggregation or stratification; after the curing is completed, the temperature and pressure are gradually reduced to normal temperature and pressure conditions, and finally the cured composite material is taken out of the hot press and subjected to subsequent mechanical processing or surface treatment.

[0042] Preferably, the electrophoretic deposition process comprises the following steps:

[0043] Placing the carbon fiber in an electrophoresis tank, wherein the electrophoresis tank is made of a corrosion-resistant polymer material and is equipped with a constant temperature control system;

[0044] Adding an electrolyte containing functionalized graphene nanosheets and nitrogen-containing carbon nanofilm precursors into an electrophoresis tank, wherein the electrolyte temperature is controlled at 25° C. to 30° C.;

[0045] Applying a DC voltage of 20V to 50V for electrophoretic deposition for a deposition time of 10 to 30 minutes;

[0046] After electrophoresis, the deposited carbon fiber is dried in a vacuum drying oven at a vacuum degree of 10^-3 to 10^-4 Torr, the temperature is controlled at 80°C to 100°C, and the drying time is 1 hour.

[0047] The cleaned and dried carbon fibers are neatly placed in an electrophoresis tank, ensuring that a certain distance is maintained between the fibers to avoid short circuits or uneven deposition caused by mutual contact; the electrophoresis tank is made of corrosion-resistant polymer materials, the inner wall of which is lined with high-temperature-resistant and chemical-resistant polytetrafluoroethylene (PTFE), and is equipped with a constant temperature control system to ensure that the electrolyte temperature in the tank is maintained between 25°C and 30°C; then, an electrolyte containing functionalized graphene nanosheets and nitrogen-containing carbon nanofilm precursors is added to the electrophoresis tank, 1% to 3% of a dispersant is added to the electrolyte to prevent agglomeration of the nanosheets, and a magnetic stirrer is used to stir the electrolyte at a speed of 200 to 500 rpm, so that the functionalized graphene nanosheets and nitrogen-containing carbon nanofilm precursors in the electrolyte are evenly distributed; during the electrophoretic deposition process, a DC voltage of 20V to 50V is applied through a voltage regulator, and the current density is controlled at 5 to 15mA / cm 2 The duration is between 10 and 30 minutes, so that the functionalized graphene nanosheets and nitrogen-containing carbon nanofilms are evenly deposited on the surface of the carbon fiber to form a nanocomposite coating; after the electrophoresis is completed, the carbon fiber is taken out of the electrophoresis tank, the residual electrolyte on the surface is thoroughly rinsed with deionized water, and dried in a vacuum drying oven. The vacuum degree is maintained at 10^-3 to 10^-4 Torr, the temperature of the drying oven is controlled at 80℃ to 100℃, and the drying time is 1 hour to ensure the adhesion and uniformity of the deposited layer.

[0048] Preferably, the mixing process of the bisphenol A modified epoxy resin and the toughening agent comprises the following steps:

[0049] Mixing bisphenol A modified epoxy resin and 3%-5% polyethylene glycol (PEG) lithium ion salt in a magnetic stirrer, controlling the stirring temperature at 50° C. to 70° C. for 1 hour;

[0050] 5% to 10% of carboxyl-terminated nitrile rubber (CTBN) and 1% to 3% of polytetrafluoroethylene (PTFE) particles were gradually added to the mixture, and uniformly dispersed using a high shear mixer for 30 minutes;

[0051] The mixture was allowed to stand at room temperature for 24 hours to ensure full integration of the toughening agent and the epoxy resin.

[0052] The mixing treatment of bisphenol A modified epoxy resin and toughening agent comprises the following steps: firstly, placing bisphenol A modified epoxy resin and 3%-5% polyethylene glycol (PEG) lithium ion salt in a constant temperature magnetic stirrer for mixing, the stirring temperature is controlled at 50°C to 70°C, and the stirring time is 1 hour, so as to ensure that the polyethylene glycol (PEG) lithium ion salt is completely dissolved and evenly distributed in the epoxy resin; then, while stirring, gradually adding 5%-10% of carboxyl-terminated nitrile rubber (CTBN) and 1%-3% of polytetrafluoroethylene (PTFE) particles into the mixture, dispersing them at a speed of 2000 to 3000 rpm by using a high shear mixer, and the mixing time is 30 minutes, so as to ensure that the toughening agent is fully mixed with the epoxy resin, and the toughening agent particles are evenly distributed in the resin; finally, the mixture is left to stand at room temperature for 24 hours, so that complete physical and chemical interactions occur between the components, so as to ensure good fusion of the toughening agent and the epoxy resin, and form a uniform and stable composite material matrix.

[0053] Preferably, the surface carboxylation treatment of the nano aluminum powder and the low-temperature freezing treatment of the aluminum-based resin include the following steps:

[0054] The nano aluminum powder is placed in a reaction kettle, and a 3% volume concentration nitric acid solution is added, and the reaction temperature is controlled at 60° C. to 80° C. and the reaction time is 2 hours to achieve carboxylation of the aluminum powder surface;

[0055] After the reaction is completed, the nano-aluminum powder is washed with deionized water to neutrality, and the water is removed by centrifugal separation and vacuum drying;

[0056] The carboxylated nano-aluminum powder is added to the aluminum-based resin mixture, and the mixture is frozen in a liquid nitrogen freezer with the temperature controlled at -80°C to -100°C for 30 to 60 minutes to improve the dispersibility of the aluminum phosphide nanoparticles.

[0057] The surface carboxylation treatment of nano aluminum powder and the low-temperature freezing treatment of aluminum-based resin include the following steps: first, placing the nano aluminum powder in an acid-resistant high-pressure reactor, adding a nitric acid solution with a volume concentration of 3% into the reactor, and controlling the reaction temperature between 60°C and 80°C by a precise temperature control system, and the reaction time is 2 hours, so as to ensure that uniform carboxyl functional groups are generated on the surface of the aluminum powder and enhance its compatibility with the resin; after the reaction, separating the nano aluminum powder from the nitric acid solution by a continuous centrifugal separation device, washing it with deionized water for multiple times until the pH value is restored to neutral, and then drying it at 60°C to 80°C by a vacuum dryer, so as to ensure that the aluminum powder particles are completely dehydrated; finally, adding the nano aluminum powder after the carboxylation treatment into the aluminum-based resin mixture, and placing the entire mixture in a liquid nitrogen freezer for freezing treatment, the freezing temperature is controlled at -80°C to -100°C, and the treatment time is 30 to 60 minutes, and the dispersibility of the aluminum phosphide nanoparticles in the resin matrix is ​​improved by means of low-temperature freezing, so as to prevent the particles from agglomerating under high temperature environment.

[0058] Preferably, the lamination process using an adjustable pressure hot press comprises the following steps:

[0059] Using a hot press equipped with a precision pressure sensor and a programmable pressure regulation system, wherein the pressing plate of the hot press is made of high-strength steel;

[0060] During the lamination process, a pressure ranging from 2MPa to 5MPa is gradually applied, and the specific pressure is adjusted according to the number of layers and thickness of the composite material;

[0061] During the pressure application process, the temperature of the hot press is controlled at 120°C to 150°C to ensure full contact and bonding between the carbon fiber and the aluminum-based resin;

[0062] After curing is completed, the composite material is cooled to room temperature by slowly reducing the pressure and temperature to avoid the generation of internal stress in the material.

[0063] Specifically, the adjustable pressure hot press used in the lamination process includes the following steps: first, a hot press equipped with a precision pressure sensor and a programmable pressure adjustment system is used, the upper and lower pressing plates of the hot press are made of high-strength steel, and the temperature of the pressing plates is evenly distributed through a built-in heating device; during the lamination process, a pressure of 2MPa to 5MPa is gradually applied according to the number of layers and thickness of the composite material to ensure sufficient contact between the layers of the material, and the pressure application rate is controlled at 0.5MPa / min to prevent rapid pressurization from causing deformation of the internal structure of the material; while the pressure is applied, the temperature of the hot press is set at 120°C to 150°C, and a precise temperature control system is used to ensure that each layer of material is evenly heated during the curing process, thereby ensuring good interface bonding between the resin and carbon fiber in the composite material; after the curing is completed, the pressure and temperature are gradually reduced through a control program, and the cooling rate is controlled at 2°C / min to avoid internal stress and microcracks in the material during rapid cooling, and finally the composite material is cooled to room temperature to ensure the overall mechanical properties of the material.

[0064] The present invention provides a temperature-mediated carbon fiber surface modification method for strengthening an aluminum-based resin material optimization method. It has the following beneficial effects:

[0065] 1. The present invention adopts amino-functionalized graphene nanosheet coating and plasma enhanced chemical vapor deposition (PECVD) technology to obtain a more uniform and active surface structure on the carbon fiber surface, and introduces a nano-scale functional layer and a nitrogen-containing carbon nanofilm on the carbon fiber surface, so that the carbon fiber can form a stronger chemical bond at the contact interface with the resin matrix. This surface modification process not only improves the chemical activity of the carbon fiber surface, enhances the wettability and interface bonding force, but also significantly reduces the peeling, fracture and other problems caused by poor interface, effectively improves the performance of composite materials under complex mechanical conditions, and is suitable for the preparation of composite materials with high strength and high reliability requirements.

[0066] 2. The present invention effectively solves the problem of agglomeration of nanoparticles in epoxy resin in the prior art by subjecting nanoaluminum powder to carboxylation and combining it with ultrasonic dispersion technology. The surface activity of nanoaluminum powder is significantly enhanced through carboxylation treatment, and it can be more evenly dispersed in the resin matrix, thereby improving the thermal conductivity of the composite material and greatly reducing the agglomeration of aluminum powder particles, so that the composite material can maintain good thermal conductivity in a high temperature environment, meeting the demand for high thermal conductivity materials in the fields of aerospace, electronic equipment, etc.

[0067] 3. The present invention effectively solves the problem of uneven dispersion of tougheners in the prior art through a high shear mixing process of bisphenol A modified epoxy resin and toughener. The high shear mixer can evenly disperse the toughener (CTBN, PTFE, etc.) in the epoxy resin matrix at a higher speed, and through a static fusion process, ensure that the toughener is fully combined with the epoxy resin. This process significantly enhances the impact resistance and toughness of the composite material, so that the material has a higher ability to resist cracking and damage when used for a long time or subjected to impact loads. In addition, by combining a programmable hot press and low-frequency vibration assisted curing technology, it can ensure that the stress distribution of the composite material during the curing process is more uniform, and the internal structure of the material is more stable, thereby significantly improving the durability and overall mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 It is a process framework diagram of the present invention. DETAILED DESCRIPTION

[0069] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] Please see attached Figure 1 :

[0071] Example 1: Carbon fiber surface modification and drying process by impregnation of amino functionalized graphene nanosheets

[0072] step:

[0073] Carbon fiber surface cleaning and pretreatment: After cutting the carbon fiber material into samples of uniform size, ultrasonic cleaning is performed in sequence. First, the carbon fiber sample is placed in an ultrasonic cleaner filled with deionized water for 10 minutes; then it is transferred to an ethanol solution for further cleaning for 10 minutes, and finally cleaned in an acetone solution for 10 minutes to ensure that there is no oil, dust or other contaminants remaining on the carbon fiber surface. After cleaning, the carbon fiber sample is placed in a vacuum drying oven at 80°C for 2 hours to ensure that the sample is completely dry.

[0074] Preparation of impregnation solution: Add amino functionalized graphene nanosheet solution to the impregnation tank, with a mass concentration of 1%-5% of nanosheets in the solution, and add 2% of dispersant (such as polyethylene glycol) to prevent the agglomeration of nanosheets. Stir at 500rpm for 30 minutes with a mechanical stirring device to make the solution uniform and ensure that the nanosheets are completely dispersed in the solution. Control the temperature in the impregnation tank between 25℃ and 30℃ to ensure that it is processed at room temperature to avoid agglomeration or degradation of nanosheets at too high a temperature.

[0075] Carbon fiber impregnation: Immerse the dried carbon fiber samples one by one into the prepared amino functionalized graphene nanosheet solution. The samples must be completely immersed in the solution. Start the thermostatic control system of the impregnation tank and keep the temperature stable at 25°C to 30°C. Use a magnetic stirring device to continuously stir the impregnation solution at a speed of 200rpm to ensure that the nanosheets are evenly distributed and can fully contact the carbon fiber surface. The impregnation time is set to 30 to 60 minutes.

[0076] Drying: Take the impregnated carbon fiber out of the solution, gently shake off the excess solution, and then put it into a preheated blast drying oven at 100℃ to 150℃. During the drying process, ensure that the airflow in the drying oven is evenly distributed and the temperature fluctuation is controlled within ±2℃ to prevent uneven coating thickness. The drying time is set to 1 to 2 hours. After drying, check the uniformity and integrity of the sample surface coating. After drying, gradually cool the sample to room temperature and store it in a sealed environment for the next step.

[0077] Innovations compared to existing technologies:

[0078] This embodiment introduces amino functionalized graphene nanosheets, which are evenly coated on the surface of carbon fiber through an impregnation process, which not only enhances the interfacial bonding strength between carbon fiber and resin, but also improves the chemical reaction activity of the carbon fiber surface through the amino function of the nanosheets.

[0079] The addition of dispersants, through the use of appropriate amounts of dispersants and the optimization of the stirring system, avoids the agglomeration of nanosheets and ensures the uniformity and adhesion of the coating, which is less involved in the prior art.

[0080] Effects and functions:

[0081] Through this modification method, the chemical activity and interfacial wettability of the carbon fiber surface are significantly improved, making it more firmly bonded with the resin matrix and improving the overall mechanical properties of the composite material.

[0082] The uniform distribution of nanosheets on the surface enhances the electrical and thermal conductivity of the interface, which is particularly important for the application of high-performance composite materials and is suitable for the preparation of high-end materials in the aerospace and automotive fields.

[0083] Example 2: Carbon fiber modification process for depositing nitrogen-containing carbon nanofilm by plasma enhanced chemical vapor deposition (PECVD)

[0084] step:

[0085] PECVD system preparation: First, thoroughly clean the PECVD reaction chamber to ensure that there is no residue inside. The chamber is made of high-purity quartz material with excellent corrosion resistance and high vacuum sealing. The initial vacuum degree in the chamber is reduced to 10^-5Torr by a vacuum pump to ensure that no impurity gas enters during the subsequent deposition process. Then check the alignment of the electrode plates in the chamber to ensure that the electric field between the electrodes is evenly distributed.

[0086] Carbon fiber sample placement: The carbon fiber sample that has been coated with amino-functionalized graphene nanosheets and dried is evenly placed on the graphite bracket of the PECVD chamber. The bracket must be kept at a certain distance from the electrode of the reaction chamber to ensure the uniformity of the electric field during the deposition process.

[0087] Reaction gas introduction and plasma excitation: Methane (CH4) and ammonia (NH3) are introduced as reaction gases through mass flow controllers, and the flow ratio is controlled between 1:1 and 1:3 (preferably 1:2) to ensure that the stoichiometric ratio of the gas mixture is appropriate. A 13.56MHz RF power supply is used to excite the plasma, and the RF power is set to 100 to 200W (preferably 150W) to promote the generation of active particles of carbon and nitrogen. The working pressure of the reaction chamber is controlled between 10^-2 and 10^-3Torr to optimize the rate and uniformity of the deposition process.

[0088] Deposition process: The plasma state is maintained in the reaction chamber for 15 to 30 minutes (preferably 20 minutes) to gradually deposit the nitrogen-containing carbon nanofilm on the surface of the carbon fiber. During this process, the high-energy particles in the plasma react chemically with the surface of the carbon fiber to form an interface layer with higher chemical activity. The deposition rate is monitored to ensure uniform thickness of the deposited layer and to avoid surface defects caused by excessive deposition.

[0089] Post-processing: After deposition is completed, the RF power supply is gradually turned off, the gas supply is stopped, and the vacuum degree in the chamber is maintained by a vacuum pump, while the temperature in the chamber is reduced to room temperature. After the carbon fiber sample is taken out of the chamber, the surface is inspected to ensure the uniformity and integrity of the deposited layer.

[0090] Innovations compared to existing technologies:

[0091] This embodiment deposits nitrogen-containing carbon nanofilms using PECVD technology. Compared with traditional surface modification methods, the chemical activity of the carbon fiber surface is improved. At the same time, the thickness and structure of the film are controlled during the deposition process to ensure the uniformity of the film.

[0092] By optimizing the gas flow ratio and RF power settings, the plasma generation is made more stable, thereby improving the deposition efficiency and reducing surface defects.

[0093] Effects and functions:

[0094] This method greatly improves the interfacial bonding ability between carbon fiber and resin matrix, and increases the corrosion resistance and oxidation resistance of the material through the presence of the film, making it suitable for application in harsh working environments.

[0095] The chemical activity of thin film deposition enhances the reactivity of the interface, greatly improving the bonding strength between carbon fiber and resin, making it suitable for the manufacture of high-performance structural materials.

[0096] Example 3: High temperature vacuum heat treatment carbon fiber surface enhancement process

[0097] step:

[0098] Vacuum furnace preparation: Use a high-temperature vacuum furnace to heat treat the carbon fiber. The furnace lining is made of high-temperature resistant graphite material to improve the stability of the furnace at high temperatures and avoid chemical contamination of the material. Start the vacuum pump and gradually reduce the vacuum degree in the furnace to 10^-6Torr to ensure that the carbon fiber surface will not be oxidized or interfered by external impurities during the treatment process.

[0099] Carbon fiber placement: Place the PECVD treated carbon fiber sample flatly on the graphite tray in the furnace, and keep the tray at an appropriate distance from the furnace wall to ensure that the carbon fiber is heated evenly during the heating process. Use the automatic temperature control system to set the heating curve, and control the heating rate at 5℃ / minute to prevent thermal stress or structural deformation of the carbon fiber material due to excessively rapid heating.

[0100] Heat treatment process: When the temperature in the furnace reaches 200°C, continue to increase the temperature to 250°C at a constant heating rate (5°C / minute) and maintain this temperature for 1 to 2 hours (preferably 1.5 hours). At this time, the surface structure of the carbon fiber is reconstructed and stabilized at high temperature, and the surface chemical activity is further enhanced. During the treatment process, the temperature fluctuation in the furnace is continuously monitored and the vacuum environment is kept stable.

[0101] Cooling and sampling: After the heat treatment, gradually reduce the temperature in the furnace, and set the cooling rate to 2°C / minute to ensure that the sample will not produce cracks or internal stress due to rapid cooling during the cooling process. After the temperature drops to room temperature, take out the carbon fiber sample and perform an appearance inspection to ensure that there is no ablation or other defects on the surface.

[0102] Innovations compared to existing technologies:

[0103] This embodiment introduces a high-temperature vacuum heat treatment process. Compared with traditional heat treatment, this process prevents the risk of carbon fiber surface oxidation by heating under high vacuum conditions and ensures the stability of the surface nano-film structure at high temperatures.

[0104] A precision temperature control system has been added to avoid thermal stress and internal defects in the material during processing by accurately controlling the heating rate and temperature, thereby improving the thermal stability of the material.

[0105] Effects and functions:

[0106] Through high-temperature vacuum heat treatment, the heat resistance and structural stability of carbon fiber are improved, enabling it to maintain excellent mechanical properties in high-temperature working environments.

[0107] The improved stability of the surface nanofilm contributes to the durability of the composite material over long-term use, making it suitable for structural applications that require long life and high reliability.

[0108] Example 4: Carboxylation of Nano-aluminum Powder and Ultrasonic Dispersion of Aluminum-Based Resin

[0109] step:

[0110] Carboxylation treatment: Place nano-aluminum powder with a particle size of 10 to 50 nm in a reactor, add 3% nitric acid solution, control the reactor temperature between 60°C and 80°C, and react for 2 hours. Use a stirrer to evenly stir the reactants at a speed of 500 rpm to ensure that the surface of the nano-aluminum powder can fully react with nitric acid to produce carboxyl functional groups. After the reaction is completed, rinse the aluminum powder with deionized water several times until the pH value is close to neutral.

[0111] Centrifugation and drying: Aluminum powder is separated from water by high-speed centrifugal separation equipment at a speed of 5000rpm for 10 minutes. The aluminum powder after centrifugation is transferred to a vacuum drying oven with a temperature set at 80°C and a vacuum degree maintained at 10^-4Torr for 1 hour to ensure that there is no residual moisture in the aluminum powder particles.

[0112] Ultrasonic dispersion: The carboxylated nano-aluminum powder is gradually added to the pre-mixed bisphenol A modified epoxy resin matrix and treated with an ultrasonic dispersion device. The ultrasonic frequency is set to 40kHz and the treatment time is 30 minutes to ensure that the aluminum powder is evenly dispersed in the resin matrix to avoid agglomeration.

[0113] Innovations compared to existing technologies:

[0114] This embodiment adds a carboxylation treatment step of the nano-aluminum powder, and improves the dispersibility of the nano-aluminum powder in the resin and the bonding force with the resin matrix through surface functionalization.

[0115] Ultrasonic dispersion technology is used to fully disperse the nanoparticles in the resin through high-frequency vibration, avoiding the agglomeration phenomenon that may be caused by traditional stirring methods.

[0116] Effects and functions:

[0117] The combination of carboxylation treatment and ultrasonic dispersion makes the dispersion of nano-aluminum powder in the resin more uniform, improves the thermal conductivity, mechanical strength and fatigue resistance of the composite material, and is suitable for the preparation of high thermal conductivity composite materials.

[0118] This process significantly improves the interfacial bonding strength of composite materials and is particularly suitable for demanding engineering structural material applications such as aerospace and electronic packaging.

[0119] Example 5: Composite material curing and low frequency vibration assisted process using a programmable hot press

[0120] step:

[0121] Material prefabrication and lamination: The surface-modified carbon fiber and aluminum-based resin materials are laminated in a specific order to form a prefabricated laminate structure. The aluminum-based resin should be fully infiltrated between each layer of fiber to avoid air inclusions and voids.

[0122] Initial curing treatment: Place the composite material in a programmable hot press, set the temperature to 90°C, and apply an initial pressure of 3MPa. Maintain the temperature and pressure conditions for 1.5 hours to ensure that the resin matrix undergoes initial cross-linking and that the carbon fiber and resin interface form an initial bond. During the initial curing period, the temperature and pressure are continuously monitored to avoid fluctuations that affect the material quality.

[0123] Secondary curing and low-frequency vibration assistance: After the initial curing is completed, the temperature of the hot press is gradually increased to 130°C, the pressure is increased to 5MPa, and maintained for 3 hours. At the same time, a low-frequency vibration of 40 to 60Hz is applied through the built-in vibration generator of the hot press, the vibration amplitude is set to 1mm, and the continuous vibration time is 2 hours. This process helps to enhance the uniform distribution of aluminum powder inside the resin, prevent particle agglomeration, and improve the overall mechanical properties of the material.

[0124] Cooling and cooling: After curing, gradually reduce the temperature and pressure, set the cooling rate to 2°C / minute, and finally cool the material to room temperature, and release the pressure slowly to avoid the generation of internal stress in the material. After cooling to room temperature, take out the composite material and inspect its appearance and mechanical properties.

[0125] Innovations compared to existing technologies:

[0126] This embodiment uses a programmable hot press and low-frequency vibration-assisted curing technology to introduce vibration assistance into the traditional hot pressing curing process, which effectively improves the fluidity inside the resin and the uniform distribution of aluminum powder particles.

[0127] The hot press has been equipped with programmed control and vibration frequency adjustment, which can adjust the temperature, pressure and vibration frequency according to the requirements of different materials to meet the manufacturing needs of various composite materials.

[0128] Effects and functions:

[0129] The vibration-assisted technology effectively reduces the voids inside the resin and enhances the dispersion of aluminum powder and resin, thereby significantly improving the mechanical properties and structural stability of the composite material.

[0130] The application of programmable hot press improves the flexibility of the production process, is suitable for the precise control manufacturing of multi-layer composite materials, and is suitable for large-scale production applications of high-end structural materials.

[0131] Test experiment process and experimental data

[0132] In order to verify the effects of the above five embodiments on carbon fiber surface modification and aluminum-based resin composite material reinforcement, tests of different performance indicators were carried out. The test experiment includes the following test process:

[0133] Tensile strength test: Test the tensile strength of the composite material to measure the bonding strength between the modified carbon fiber and the resin.

[0134] Shear strength test: Test the shear strength at the interface between carbon fiber and resin.

[0135] Thermal conductivity test: Test the thermal conductivity of the composite material to verify the effect of the dispersion of aluminum powder on the thermal conductivity of the composite material.

[0136] Impact toughness test: Test the impact resistance of composite materials under external impact and evaluate the toughening effect.

[0137] Conductivity Test: Test the conductivity of composite materials to evaluate their electrical conductivity.

[0138] Test experiment process

[0139] Sample preparation: 5 samples were cut from the composite material prepared in each example, each sample had a size of 100 mm×100 mm×5 mm, and all samples were ensured to have smooth surfaces and consistent sizes.

[0140] Tensile strength test process:

[0141] Using a tensile tester, clamp the sample in the fixture of the instrument, test at a speed of 2 mm / min, and measure the stress-strain curve of the sample under different tensile forces.

[0142] Data recording: record the yield point and breaking point of the sample and calculate the tensile strength.

[0143] Shear strength test process:

[0144] The shear strength between carbon fiber and resin was measured by shearing the sample at an angle of 45° and a test speed of 1 mm / min.

[0145] Data recording: record the maximum shear force and calculate the shear strength.

[0146] Thermal conductivity test process:

[0147] The thermal conductivity of the samples was measured at different temperatures, ranging from 25°C to 150°C, using a thermal conductivity tester.

[0148] Data recording: Record thermal conductivity every 25°C and analyze changes in thermal conductivity.

[0149] Impact toughness test process:

[0150] Use an impact tester to hit the sample with a pendulum and measure the impact energy absorbed by the sample.

[0151] Data recording: record the absorbed energy of the sample and calculate the impact toughness.

[0152] Conductivity test process:

[0153] Use a four-probe conductivity tester to test the conductivity of the sample at room temperature. Data recording: Measure the resistivity of the sample and calculate the conductivity.

[0154] Experimental data and results

[0155] Table 1: Tensile strength test results of the composite materials of various embodiments (MPa)

[0156] Example Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 average value Example 1 450.2 455.3 448.1 453.6 451.9 451.82 Example 2 470.5 473.2 472.0 471.5 469.8 471.40 Example 3 435.8 438.0 440.1 437.5 436.7 437.62 Example 4 460.3 462.7 461.9 463.2 461.1 461.84 Example 5 475.0 478.5 476.2 474.6 477.8 476.42

[0157] Table 2: Shear strength test results of the composite materials of various embodiments (MPa)

[0158] Example Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 average value Example 1 450.2 455.3 448.1 453.6 451.9 451.82 Example 2 470.5 473.2 472.0 471.5 469.8 471.40 Example 3 435.8 438.0 440.1 437.5 436.7 437.62 Example 4 460.3 462.7 461.9 463.2 461.1 461.84 Example 5 475.0 478.5 476.2 474.6 477.8 476.42

[0159] Table 3: Thermal conductivity test results of the composite materials of various embodiments (W / m·K)

[0160] Temperature(℃) Example 1 Example 2 Example 3 Example 4 Example 5 25 1.2 1.5 2.8 1.4 3.1 50 1.3 1.6 2.9 1.5 3.2 75 1.4 1.7 3.0 1.6 3.3 100 1.5 1.8 3.1 1.7 3.4 125 1.6 1.9 3.2 1.8 3.5 150 1.7 2.0 3.3 1.9 3.6

[0161] Table 4: Impact toughness test results of the composite materials of each embodiment (kJ / m 2 )

[0162]

[0163]

[0164] Table 5: Conductivity test results of the composite materials of various embodiments (S / m)

[0165] Example Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 average value Example 1 50.3 51.2 50.9 51.0 50.8 50.84 Example 2 55.1 54.9 55.2 55.0 54.8 55.00 Example 3 48.7 49.1 49.0 48.8 49.2 48.96 Example 4 53.4 53.6 53.1 53.5 53.3 53.38 Example 5 57.2 57.5 57.1 57.3 57.4 57.30

[0166] Test Results Summary

[0167] Tensile strength: Example 5 has the highest tensile strength, reaching 476.42 MPa, which shows that the low-frequency vibration auxiliary technology in this process effectively improves the tensile properties of the material and ensures the uniform distribution and interface bonding inside the material. The PECVD treatment in Example 2 also significantly enhances the tensile properties.

[0168] Shear strength: The shear strength of Example 5 (92.52 MPa) is also the highest, further verifying the importance of low-frequency vibration in the curing process. Example 2 treated with PECVD is close behind, indicating that the nitrogen-containing carbon film on the surface has a great promoting effect on the interface bonding.

[0169] Thermal conductivity: Examples 3 and 5 exhibited high thermal conductivity at all temperatures, especially at 150°C, where the thermal conductivity of Example 5 reached 3.6 W / m·K, which was due to the good dispersion and carboxylation of the nano-aluminum powder. Example 3 also exhibited good thermal conductivity.

[0170] Impact toughness: Example 5 has the highest impact toughness, which is 15.10 kJ / m 2 , which is significantly higher than that of other embodiments, indicating that the toughening treatment and vibration assistance have better effects. Embodiments 2 and 4 also show higher impact toughness.

[0171] Conductivity: The conductivity of Example 5 is 57.30 S / m, indicating that the dispersibility of nano-aluminum powder and the interface modification of carbon fiber effectively improve the dielectric properties. Example 2 and Example 4 are second.

[0172] Summary and Analysis

[0173] Example 5: Excellent performance in all tests, especially in mechanical properties (tensile and shear strength), electrical conductivity and thermal conductivity, thanks to the process optimization of low-frequency vibration assistance and programmable hot press.

[0174] Example 2: The effect of PECVD treatment is remarkable, especially in terms of interface bonding strength. Its tensile and shear strengths are second only to those of Example 5, and its dielectric properties are relatively high.

[0175] Example 3: The performance in the thermal conductivity test was outstanding, indicating that the carboxylation treatment and ultrasonic dispersion of the nano-aluminum powder effectively improved the thermal conductivity.

[0176] Example 1 and Example 4: Although they performed well in terms of electrical conductivity and impact toughness, they were slightly inferior to other examples in terms of tensile strength and shear strength.

[0177] Comparative experiment 1: Effect of carbon fiber surface modification on interfacial bonding strength

[0178] Purpose:

[0179] The difference in the bonding strength between the carbon fiber and resin interface between the carbon fiber surface modification process of the present invention using amino functionalized graphene nanosheet coating + PECVD nitrogen-containing carbon nanofilm deposition and the traditional acid treatment process in the prior art is compared.

[0180] Existing technical solutions:

[0181] Traditional acid treatment: The carbon fiber is placed in a nitric acid / sulfuric acid mixed solution for chemical oxidation for 30 minutes at a treatment temperature of 60°C, followed by rinsing with deionized water and drying. This process can increase the oxygen-containing functional groups on the surface of the carbon fiber and enhance the interfacial bonding strength.

[0182] Technical solution of the present invention:

[0183] Amide-functionalized graphene nanosheet impregnation and PECVD treatment: The carbon fiber surface is first impregnated with an amino-functionalized graphene nanosheet solution, and then a nitrogen-containing carbon nanofilm is deposited by PECVD to improve the chemical activity and wettability of the carbon fiber surface.

[0184] Testing process:

[0185] Sample preparation: Two groups of samples were prepared, one group using the traditional acid treatment technology (existing technology), and the other group using the amino graphene nanosheets and PECVD modification treatment of the present invention (the present invention).

[0186] Interface shear strength test: Use a shear strength tester to perform a 45° shear test on the two groups of samples at a test speed of 1 mm / min, and record the maximum shear force and corresponding shear strength of each group of samples.

[0187] Surface morphology and chemical composition analysis: Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) were used to analyze the morphology and chemical composition of the two groups of carbon fibers and evaluate their surface modification effects.

[0188] Experimental data table 1: Interface shear strength test results (MPa)

[0189] Sample No. Prior art The present invention Sample 1 70.2 85.6 Sample 2 69.8 86.1 Sample 3 71.0 85.9 Sample 4 70.5 86.3 Sample 5 69.5 86.0 average value 70.2 85.98

[0190] Experimental data table 2: SEM and XPS analysis results

[0191]

[0192] Comparative analysis:

[0193] Interface bonding strength: The shear strength of the present invention is significantly higher than that of the prior art (85.98 MPa vs. 70.2 MPa), indicating that nanographene and PECVD treatment significantly enhance the bonding strength between carbon fiber and resin.

[0194] Surface morphology and chemical composition: SEM shows that the treatment technology of the present invention forms a uniform micro-nano structure on the surface of the carbon fiber, and XPS shows that the introduction of nitrogen element improves the chemical reaction activity of the interface.

[0195] Comparative experiment 2: Effect of nano-aluminum powder dispersion on thermal conductivity of composite materials

[0196] Purpose:

[0197] The difference in thermal conductivity of the composite material between the nano aluminum powder carboxylation treatment + ultrasonic dispersion technology used in the present invention and the traditional mechanical stirring dispersion in the prior art is compared.

[0198] Existing technical solutions:

[0199] Traditional mechanical stirring dispersion: Add the untreated nano aluminum powder into the epoxy resin through a mechanical stirrer at a stirring speed of 1000 rpm for 30 minutes. This method mainly relies on physical mixing, and the particles are prone to agglomeration.

[0200] Technical solution of the present invention:

[0201] Nano-aluminum powder carboxylation treatment + ultrasonic dispersion: Nano-aluminum powder is carboxylated with nitric acid solution to enhance surface activity, and then an ultrasonic dispersion device is used for 40kHz vibration dispersion for 30 minutes to ensure uniform distribution of nanoparticles.

[0202] Testing process:

[0203] Sample preparation: Two groups of samples were prepared, one group was dispersed by conventional mechanical stirring (existing technology), and the other group was dispersed by carboxylation treatment + ultrasonic wave (the present invention).

[0204] Thermal conductivity test: Use a thermal conductivity tester to measure the thermal conductivity of two groups of samples at different temperatures (25°C to 150°C), and record the data every 25°C.

[0205] Particle dispersion analysis: Transmission electron microscopy (TEM) was used to analyze the nanoparticle dispersion of the two groups of samples.

[0206] Experimental data table 3: Thermal conductivity test results of composite materials (W / m·K)

[0207]

[0208]

[0209] Experimental data table 4: TEM particle dispersion analysis results

[0210] Dispersion Technology Average particle agglomeration diameter (nm) Dispersion uniformity (%) Prior art 150 60 The present invention 50 90

[0211] Comparative analysis:

[0212] Thermal conductivity: The thermal conductivity of the samples of the present invention at all temperatures is significantly higher than that of the prior art, especially at 150°C, the thermal conductivity of the present invention reaches 3.6 W / m·K, while the prior art is only 2.6 W / m·K.

[0213] Particle dispersibility: TEM analysis shows that the technology of the present invention significantly improves the dispersibility of nano-aluminum powder, greatly reduces particle agglomeration, and improves dispersion uniformity.

[0214] Comparative experiment 3: Comparison of mechanical properties of composite materials (tensile strength and impact toughness)

[0215] Purpose:

[0216] The differences in tensile strength and impact toughness of the composite material between the high shear mixing process of the bisphenol A modified epoxy resin + toughening agent in the present invention and the traditional stirring method in the prior art are compared.

[0217] Existing technical solutions:

[0218] Traditional stirring method: bisphenol A epoxy resin and toughening agent (CTBN) are mixed by a mechanical stirrer at a stirring speed of 1000 rpm for 30 minutes. The toughening agent and the resin are not evenly combined, which affects the performance of the composite material.

[0219] Technical solution of the present invention:

[0220] High shear mixing of bisphenol A modified epoxy resin + toughening agent: bisphenol A modified epoxy resin was mixed with toughening agents CTBN and PTFE using a high shear mixer at a speed of 3000 rpm for 30 minutes, followed by standing for 24 hours to ensure that the toughening agent was fully integrated with the resin.

[0221] Testing process:

[0222] Sample preparation: Two groups of samples were prepared, one using conventional mechanical stirring (prior art) and the other using high shear mixing (present invention).

[0223] Tensile strength test: The two groups of samples were subjected to a tensile strength test using a tensile tester at a test speed of 2 mm / min, and the yield point and breaking point of the samples were recorded.

[0224] Impact toughness test: Use an impact tester to measure the impact resistance of the two groups of samples, adopt a pendulum test, and record the absorbed impact energy.

[0225] Experimental data table 5: tensile strength test results (MPa)

[0226] Sample No. Prior art The present invention Sample 1 410.3 460.2 Sample 2 408.7 462.1 Sample 3 411.0 463.5 Sample 4 409.2 461.0 Sample 5 407.9 461.5 average value 409.42 461.66

[0227] Experimental data table 6: Impact toughness test results (kJ / m 2 )

[0228]

[0229]

[0230] Comparative analysis:

[0231] Tensile strength: The high shear mixing technology in the present invention significantly improves the tensile strength of the composite material, with an average value of 461.66 MPa, which is significantly higher than 409.42 MPa in the prior art, indicating that the toughening agent is more fully combined with the resin.

[0232] Impact toughness: The impact toughness of the present invention reaches 13.6 kJ / m 2 , compared with the existing technology of 10.0kJ / m 2 , indicating that the toughening agent can enhance the impact resistance of the material after being evenly distributed.

[0233] Summarize

[0234] Interface bonding strength test: The present invention significantly improves the bonding strength of the interface between carbon fiber and resin through amino functionalized graphene and PECVD treatment, which is superior to the traditional acid treatment process.

[0235] Thermal conductivity comparison: The carboxylation treatment and ultrasonic dispersion technology of the nano-aluminum powder in the present invention effectively improve the thermal conductivity of the composite material, avoid particle agglomeration, and make the dispersion more uniform.

[0236] Mechanical properties test: The high shear mixing process of the present invention improves the tensile strength and impact toughness of the composite material, is superior to the traditional mechanical stirring method, and enhances the structural stability and durability of the material.

[0237] By comparing the experimental data, it can be clearly seen that the performance of the present invention in many aspects such as interface bonding force, thermal conductivity, tensile strength, impact toughness, etc. has been significantly improved, and it has broad application prospects.

[0238] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Temperature-mediated carbon fiber surface modification to enhance aluminum-based resin material optimization method, characterized in that: The material formulation includes the following components: Carbon fibers, in a mass ratio of 35% to 45%, wherein the surface of the carbon fibers is modified by the following steps: Coating 2% to 5% by mass of amino-functionalized graphene nanosheets on the surface of carbon fibers; Then, a nitrogen-containing carbon nanofilm was deposited on the carbon fiber surface by plasma enhanced chemical vapor deposition (PECVD) to increase the interfacial chemical activity; Heat treatment at 200°C to 300°C to stabilize the surface structure and enhance interface strength; Aluminum-based resin, comprising the following components: 55% of bisphenol A modified epoxy resin, wherein 5% to 10% by mass of aluminum phosphide nanoparticles are added to the epoxy resin; 20%-30% volume fraction of nano-aluminum powder, with a particle size of 10 to 50 nanometers; 10% - 20% polyimide-based curing agent; 1% - 3% silane coupling agent; 5%-10% of a toughening agent, wherein the toughening agent comprises a mixture of carboxyl-terminated nitrile rubber (CTBN) and a fluorine-containing polymer.

2. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 1, characterized in that: The amino functionalized graphene nanosheets are coated on the surface of the carbon fiber by the following steps: Placing the carbon fiber in an immersion tank filled with an amino-functionalized graphene nanosheet solution, wherein the immersion tank is made of corrosion-resistant stainless steel and equipped with a constant temperature control system to control the temperature at 25° C. to 30° C.; The solution is evenly distributed and impregnated into the carbon fiber by a magnetic stirring device at room temperature, and the impregnation time is 30 to 60 minutes; The impregnated carbon fiber is taken out and dried in a forced air drying oven at 100° C. to 150° C. for 1 to 2 hours.

3. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 1, characterized in that: The PECVD process comprises the following steps: The carbon fiber coated with amino functionalized graphene nanosheets is placed in a PECVD reaction chamber, wherein the chamber is made of high-purity quartz material and has high vacuum sealing performance; Using methane (CH4) and ammonia (NH3) as reaction gases, the flow ratio of methane to ammonia is 1:1 to 1:3; Plasma is excited by a radio frequency power supply device, and nitrogen-containing carbon nanofilm is deposited on the surface of carbon fiber under low pressure (10^-2 to 10^-3 Torr) for 15 to 30 minutes.

4. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 1, characterized in that: The heat treatment step comprises: Use a high-temperature vacuum furnace, the furnace body is lined with high-temperature resistant graphite material and is equipped with an automatic temperature control system; The PECVD-treated carbon fiber was placed in a vacuum furnace and heated at a vacuum degree of 10^-5 to 10^-6 Torr at a heating rate of 5°C / min. When the temperature reaches 250°C, maintain this temperature for 1 to 2 hours and then slowly cool down to room temperature.

5. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 1, characterized in that: The method comprises the following steps: The modified carbon fiber is subjected to vacuum drying at a temperature of 80°C to 120°C for 1 hour; An aluminum-based resin mixture is prepared, nano-aluminum powder is dispersed in a modified epoxy resin by ultrasonic treatment, and then aluminum phosphide nanoparticles, a polyimide-based curing agent, a silane coupling agent and a toughening agent are added and high shear mixing is performed; Pre-curing the mixture at 100°C to improve the homogeneity of the mixture and fiber impregnation; The pretreated carbon fiber is laminated with an aluminum-based resin mixture and initially cured at 80°C to 100°C in a vacuum environment.

6. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 5, characterized in that: The preliminary curing and second stage curing process comprises the following steps: Use a programmable heat press equipped with a temperature and pressure control system that can precisely control the curing temperature and applied pressure; In the initial curing stage, the composite material is placed in a hot press and cured at a temperature ranging from 80°C to 100°C for 1 to 2 hours; After initial curing, the temperature of the composite material is raised to 120°C to 150°C and heated for 3 to 4 hours, while low-frequency vibrations of 40 to 60 Hz are applied through a built-in vibration generator to promote uniform distribution of aluminum powder and other nanoparticles in the resin matrix.

7. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 5, characterized in that: The electrophoretic deposition process comprises the following steps: Placing the carbon fiber in an electrophoresis tank, wherein the electrophoresis tank is made of a corrosion-resistant polymer material and is equipped with a constant temperature control system; Adding an electrolyte containing functionalized graphene nanosheets and nitrogen-containing carbon nanofilm precursors into an electrophoresis tank, wherein the electrolyte temperature is controlled at 25° C. to 30° C.; Applying a DC voltage of 20V to 50V for electrophoretic deposition for a deposition time of 10 to 30 minutes; After electrophoresis, the deposited carbon fiber is dried in a vacuum drying oven at a vacuum degree of 10^-3 to 10^-4 Torr, the temperature is controlled at 80°C to 100°C, and the drying time is 1 hour.

8. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 5, characterized in that: The mixing process of the bisphenol A modified epoxy resin and the toughening agent comprises the following steps: Mixing bisphenol A modified epoxy resin and 3%-5% polyethylene glycol (PEG) lithium ion salt in a magnetic stirrer, controlling the stirring temperature at 50° C. to 70° C. for 1 hour; 5% to 10% of carboxyl-terminated nitrile rubber (CTBN) and 1% to 3% of polytetrafluoroethylene (PTFE) particles were gradually added to the mixture, and uniformly dispersed using a high shear mixer for 30 minutes; The mixture was allowed to stand at room temperature for 24 hours to ensure full integration of the toughening agent and the epoxy resin.

9. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 5, characterized in that: The surface carboxylation treatment of the nano aluminum powder and the low-temperature freezing treatment of the aluminum-based resin include the following steps: The nano aluminum powder is placed in a reaction kettle, and a 3% volume concentration nitric acid solution is added, and the reaction temperature is controlled at 60° C. to 80° C. and the reaction time is 2 hours to achieve carboxylation of the aluminum powder surface; After the reaction is completed, the nano-aluminum powder is washed with deionized water to neutrality, and the water is removed by centrifugal separation and vacuum drying; The carboxylated nano-aluminum powder is added to the aluminum-based resin mixture, and the mixture is frozen in a liquid nitrogen freezer with the temperature controlled at -80°C to -100°C for 30 to 60 minutes to improve the dispersibility of the aluminum phosphide nanoparticles.

10. The temperature-mediated carbon fiber surface modification to enhance the optimization method of aluminum-based resin materials according to claim 5, characterized in that: The lamination process uses an adjustable pressure heat press, which includes the following steps: Using a hot press equipped with a precision pressure sensor and a programmable pressure regulation system, wherein the pressing plate of the hot press is made of high-strength steel; During the lamination process, a pressure ranging from 2MPa to 5MPa is gradually applied, and the specific pressure is adjusted according to the number of layers and thickness of the composite material; During the pressure application process, the temperature of the hot press is controlled at 120°C to 150°C to ensure full contact and bonding between the carbon fiber and the aluminum-based resin; After curing is completed, the composite material is cooled to room temperature by slowly reducing the pressure and temperature to avoid the generation of internal stress in the material.